The way of things - Butler, Melissa A (Department of English Language and Literature, 2014)
This manuscript 'the way of things' is a collection of poems that, regardless of subject matter, consistently gravitates towards an exploration of the poetics of space. In this regard, it bears a relation to the theoretical work done by Gaston Bachelard, but it also stands in relation to tradition in 20th Century poetry which deals with objects (usually of the most ordinary sort), the relation of human beings to such objects and the way such objects cast into relief certain aspects of the human condition. Whether the poems touch on a love affair, whether they describe a still life or whether they explore a metaphysical longing, their poetics is drawn from their attempt to define a space and its presence on human lives. Thus, the way of things takes its place in a long lineage of conceptual poetry and is an attempt to add to that lineage. And although the poems might appear to be primarily conceptual, this only reveals the extent to which concepts themselves can have deeply emotional and indeed lyrical implications.